Game-Based Learning Media For Number Topic: Analysis And Design - Salsabila, Nilza Humaira; Hapipi, Hapipi; Lu'luilmaknun, Ulfa (UIN Antasari, 2021)
This study aims to describe the preliminary analysis on the development of game media and see the student's preliminary response to the developed game-based mathematics learning media that is oriented to the learning outcomes of junior high school students. Several previous research results have shown that game-based learning media can improve students' mathematics learning outcomes. The development of learning media is based on the ADDIE development model which consists of five stages, namely, analysis, design, development, implementation, and evaluation. The respondents in this study were junior high school students totaling 122 people. Students are given a questionnaire related to game development. The questionnaire consists of 5 closed statement questions, with 4 answers on a Likert scale, namely strongly agree, agree, disagree, strongly disagree. The results show that most students agree that game learning media is needed in number topic, game learning media that can be played on mobile phones will make students easier to learn, the display of the game media is attractive, the color combination in the game media is interesting, and the characters in the game media are interesting.